Analisis Gender Pathway Pengarusutamaan Hak Anak SAD Dampingan Pundi Sumatra pada Isu Pendidikan - Reverawati, Wenny Ira (Harakat an-Nisa: Jurnal Studi Gender dan Anak, 2024)
This research analyzes the gender gap in access to education and women's empowerment in the Suku Anak Dalam (SAD) community assisted by Pundi Sumatera. Using descriptive qualitative method, this research explores various internal and external factors that affect the limited access, participation, control, and benefits of education for women in this community. Data were collected through interviews, observations, and review of related documents. The results show that patriarchal cultural factors, domestication of women, and lack of awareness of the importance of education are the main barriers to access and participation of SAD women in education. In addition, external factors such as limited policies that support the education of indigenous communities and the lack of collaboration between the government and community organizations also exacerbate this gap. These findings are contextualized with previous studies, which show similar patterns in other indigenous communities in Indonesia. This study recommends the need for more inclusive community-based policies, alternative education programs that respect local cultural values, and increased synergy between the government, non-governmental organizations and SAD communities to improve access and quality of education for women.